THE ARASY TOWER AS AN INSPIRATION IN CONTEMPORARY FASHION - Wella Endangsari; Nofi Rahmanita (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
My work entitled "Menara Gentala Arasy as a Source of Inspiration in Contemporary Fashion", is inspired by the architecture of the Gentala Arasy Tower and the Gentala Arasy Bridge by taking several forms and ornamens found on the tower and bridge such as the shape of a clock, ornamens on the tower and the architecture of the bridge in the form of motifs on clothing using sequin techniques that form the Gentala Arasy Bridge motif. Contemporary clothing that combines traditional nuances with futuristic elements through a combination of classic Jambi batik materials and modern american drill. The silhouette of this dress is dominated by wide, layered cuts on the sleeves, asymmetrical cuts, with tower and clock motif embroidery, giving a strong impression of local identity. In the middle there is a clock and tower motif made with a threadembroidered technique, reflecting the combination of time and architecture. The dark blue and orange colors provide a dynamic contrast, enhanced by the thread-embroidered motif on the sleeves. The choice of colors is directly inspired by the Gentala Arasy Tower, namely golden yellow, red, emerald blue, and black. The materials used are Satin Bridall, American Drill, and Batik Jambi. The creation method begins with preparation, namely conducting a field survey to find sources of ideas or themes, and formulating creative ideas to provide a better understanding of the form of work created and looking for literature or references related to the creative idea. The embodiment of the work uses the technique of connecting and boutique.